2005
DOI: 10.1203/01.pdr.0000157720.50808.97
|View full text |Cite
|
Sign up to set email alerts
|

Increased Renal Tubular Reabsorption of Calcium and Magnesium by the Offspring of Diabetic Rat Pregnancy

Abstract: Diabetic pregnancy has a marked influence on offspring calcium and magnesium homeostasis. Urinary excretion of calcium and magnesium is reduced, yet offspring of diabetic pregnancy exhibit hypomagnesemia and hypocalcemia. The aim of this study was to measure renal hemodynamic and tubular function in the offspring of diabetic (OD) and control, nondiabetic (OC) rats at 4 and 8 wk of age to determine the glomerular and tubular mechanisms through which renal calcium and magnesium handling are programmed in utero. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The hypothesis that fetal kidney expression of calcium-transporting proteins is permanently programmed by prevailing in-utero glucose and/or calcium concentrations should be tested in future experiments. Such experiments also need to examine related endocrine changes: in a separate study we have found that concentrations of serum parathyroid hormone (PTH) are reduced in 8-week-old OD rats relative to those in OC rats [30].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that fetal kidney expression of calcium-transporting proteins is permanently programmed by prevailing in-utero glucose and/or calcium concentrations should be tested in future experiments. Such experiments also need to examine related endocrine changes: in a separate study we have found that concentrations of serum parathyroid hormone (PTH) are reduced in 8-week-old OD rats relative to those in OC rats [30].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in skeletal development in offspring as a result of maternal high-fat diet [25] and in offspring of rats with streptozotocin induced diabetes [21] have been described previously. The skeletal changes we observed could stem from parental transmission of programming effects, or be the result of the metabolic abnormalities in the offspring.…”
Section: Discussionmentioning
confidence: 58%
“…In some models a strong metabolic phenotype with the development of obesity can be observed, in other models the metabolic impairment is more subtle, affecting, for example, lipid metabolism. Besides metabolic impairments [15] [17], changes of skeletal development [16], of kidney function [21], of cardiac/vascular function [18], of aortic gene expression [20], of gene expression changes in hypothalamic centers [22], changes in pancreatic beta cells [23] and changes in behavior have been described as results of either diabetic or dysmetabolic mothers. More recently there have been reports on paternal transmission of such effects as well [16] [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hematuria indicated thin basement membranes during alcohol-related dyslipidemia so that long cessation periods were needed without alcohol consumption, without sugar alcohol, saturated fat and transformed phospholipids. Women with albuminuria had to perceive that about 40% of excreted albumin is degraded during glomerular transcytosis and cannot be detected [60] [68] [69]. Urinary albumin cannot be reabsorbed and can trigger tubular fibrosis with disturbed tubular re-adsorption [60].…”
Section: Discussionmentioning
confidence: 99%